Leilões multidimensionais com escore reserva secreto - Holanda, Francisco Bruno de Lima (2012)
In this work, let’s apply auction theory to solve a parsimonious procurement model in a situation where there is a contracting firm by the Government. It’s a natural extension of the bidimensional auction model proposed by Yeon-Koo Che (1993) to model actions of the Department of Defense (DoD) in United States. The extension will be made based in a secret reservation price model proposed by Laffontet at. (1994) to unidimensional case. At end, we will make a short numerical analysis of the model proposed in this work.